The Lived Experiences of Teachers’ Teaching Oral Communication Through Modular Distance Learning during the Pandemic - Abarca, Cris Dyan (Journal of Interdisciplinary Perspectives, 2024)
During the COVID-19 pandemic, educational systems faced unprecedented challenges, necessitating rapid adaptations to ensure continued learning despite school closures. In response, the Most Essential Learning Competencies (MELCs) were implemented to prioritize key learning areas and objectives. However, the effectiveness of Modular Distance Learning (MDL) in delivering quality education, particularly in Oral Communication, has been questioned. This study examined the lived experiences of English teachers teaching Oral Communication within MDL in the Division of Negros Oriental. Utilizing a phenomenological approach and Colaizzi’s method of data analysis, the study identified four key themes: (a) Pedagogical Challenges of MDL, (b) Teaching Difficulties with MELCs, (c) Parents as Co-Educators, and (d) Administrative Navigation. These findings highlight the need for a comprehensive reevaluation of MELCs to align with diverse learning modalities. Ongoing collaborative efforts among English teachers are essential to addressing systemic educational disparities, particularly in Oral Communication instruction. Additionally, the study underscores the crucial role of parental support in facilitating student learning within MDL, emphasizing the importance of increased student engagement in Oral Communication activities. The findings advocate for improved pedagogical practices and resource allocation to ensure equitable access to quality education, especially in areas critical for holistic student development like Oral Communication.